Seismic Behavior and Finite Element Analysis of Reinforced Concrete Short Columns Impacted by Oblique Earthquakes - Chunyang Liu; Guixin Yu; Xisen Fan; Changqun Guo; Fei Li (Advances in Civil Engineering)
This study evaluates the seismic behavior of reinforced concrete (RC) short columns with a high axial compression ratio under oblique earthquake conditions. The studied parameters include the loading angle, axial compression ratio, the high-strength stirrups with small spacing, and the carbon-fiber-reinforced polymer (CFRP) wrapped column end or outer steel plate mesh at the end of the column. Low-cycle repeated loading tests were used to analyze the specimens’ seismic performance indices of hysteretic behavior, strength, stiffness, deformation capacity, and energy dissipation capacity. Results suggest that the OpenSees finite element program can sufficiently simulate the nonlinear response of the specimen. Oblique loading led to the increase of damage to the specimens and the deterioration of stiffness of the specimens, which was especially seen with the increase of the axial compression ratio. Accordingly, arranging high-strength stirrups with small spacing and the column end outer steel plate mesh both transform the failure mode from shear failure to bending shear failure. Additionally, wrapping the CFRP at the end of columns improves their strength but does not improve their deformation capacity. The demonstrated success of these strategies in improving the seismic performance of RC short columns under diagonal loads with high axial compression ratios can inform practical engineering applications.